PARITY OF THE COGNITIVE AND INFORMATION TECHNOLOGIES IN MATHEMATICAL EDUCATION ECONOMISTS - Oleg V. Tatarnikov; Anatoliy S. Chuyko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The results of studying mathematics in higher school form for researchers the foundation for the development of science and for users, including economists - the instrument for decision-making. The development of science brings new subjects to the education system, which causes the reduction of time for traditional subjects, including mathematics. The local use of information technologies cannot enable us to reach a major target of education, i. e. the development of logical thinking. The article puts forward a system approach ensuring a conformity between cognitive technologies in mathematical education of economists and information technologies used in education. The authors show that this approach must be based on monitoring the parity between the mentioned technologies in order to update the ground of sums and tasks, as well as structure, content and methods of delivering the material.